Real Estates in Cyprus: A Diary - Kockelkorn, Anne (Writingplace, 2019)
This edited ethnographic diary, produced during a research and teaching stint in Cyprus, takes in the island landscape, politics and underlying economic forces dramatically shaping the environment in order to reveal a complex picture across a variety of scales and analytical registers. The aim of this diary is to understand the recent real-estate transactions launched by the Government of the Republic of Cyprus and selling EU-Citizenship in tandem with real estate, particularly as high-end luxury development along the coast. This understanding of land ownership and real estate evolves around the notion of territoriality, which defines territory as a cultural and social product and which includes the Lefebvrian dimension of lived space. The fragmented form of the diary entry will allow to cut across the different registers mentioned above; the work of the editing process will consist in framing the subjective position of the self as a political. This text is introduced by a reading compiled by Hélène Frichot